Utility of BAP1 Immunohistochemistry and p16 (CDKN2A) FISH in the Diagnosis of Malignant Mesothelioma in Effusion Cytology Specimens. (January 2016) - Hwang, Harry C.; Sheffield, Brandon S.; Rodriguez, Stephanie; Thompson, Kim; Tse, Christopher H.; Gown, Allen M.; Churg, Andrew
Abstract : The diagnosis of malignant mesothelioma in effusion cytology specimens is controversial. BAP1 immunohistochemistry and p16 fluorescence in situ hybridization (FISH) have recently been reported as reliable markers of malignancy in biopsies of mesothelioma. To determine whether these markers, singly or in combination, might also be useful in effusion cytology specimens, we examined 15 biopsies of epithelial mesotheliomas and 3 benign mesothelial reactions and corresponding effusion cytology paraffin-embedded cell blocks. Four cytology specimens were too scanty for p16 FISH analysis but were interpretable for BAP1 immunohistochemistry. Overall, loss of BAP1 and/or deletion of p16 was seen in 11/11 (100%) of matched cytology and tissue biopsy specimens. BAP1 loss alone was seen in 10/15 (67%) biopsies and 10/15 (67%) cytology specimens. Homozygous deletion of p16 by FISH was found in 12/15 (80%) biopsy specimens and 8/11 (73%) evaluable cytology specimens. Seven of 15 (47%) biopsies and 5/11 (42%) cytology specimens showed loss of both markers. All mesothelioma biopsy/cytology pairs showed exactly the same pattern of BAP1 or p16 retention or loss in the biopsy and cytology specimens. The 2 peritoneal mesothelioma cases demonstrated loss of BAP1 but not p16. None of the benign mesothelial reactions or corresponding cytology specimens showed loss of either marker. We conclude that both BAP1 immunohistochemistry and p16 FISH analysis provide reliable markers of mesothelial malignancy in effusion cytology specimens, especially where the atypical mesothelial proliferation is well sampled. BAP1 is easier to interpret with scanty specimens. On the basis of small numbers of cases, use of both markers appears to increase sensitivity.